2006
DOI: 10.1557/proc-0929-ii04-12
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on Thermoelectric Characteristics of Layered Nanostructure by Ion Beam Bombardment

Abstract: We made p-type nanoscale super lattice thermoelectric cooling devices which consist of multiple periodic layers of Si1−x Gex / Si, The thickness of each layer ranges between 10 and 50 nm. The super lattice was bombarded by 5 MeV Si ion with different fluencies aiming to form nano-cluster quantum dot structures. We estimated the thermo-electric efficiency of the so fabricated devices, measuring the thin film cross plane thermal conductivity by the 3rd harmonic method, measuring the cross plane Seebeck coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The size of the Si/Ge multilayer thin film for Seebeck coefficient measurement is 2 mm × 7 mm. The experimental setup for Seebeck coefficient measurement was previously reported elsewhere [16]. Fig.…”
Section: Thermoelectric Measurements and Resultsmentioning
confidence: 99%
“…The size of the Si/Ge multilayer thin film for Seebeck coefficient measurement is 2 mm × 7 mm. The experimental setup for Seebeck coefficient measurement was previously reported elsewhere [16]. Fig.…”
Section: Thermoelectric Measurements and Resultsmentioning
confidence: 99%
“…A metal (Au) contact layer was deposited on the SiO 2 substrate before and after the deposition of monolayer SiGe thin film to enable an electrical contact for the Seebeck coefficient measurement. The high energy ion bombardment can produce nanostructures and modify the property of thin films [9,10], resulting in lower thermal conductivity and higher electrical conductivity. While fig.1a shows the film geometry used for the electrical and thermal conductivity measurements, fig.2b shows the film geometry used for Seebeck coefficient measurement.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…In previous studies we have demonstrated the improved thermoelectric properties of SiO2 MLs embedded with various nanoparticles, such as Au, Ag and Cu [9][10][11][12]. ML structures are fabricated to reduce the phonon conduction through the sample, thus increasing the figure of merit.…”
Section: Introductionmentioning
confidence: 99%
“…is the electrical conductivity, T is the absolute temperature, and is the thermal conductivity [10,11]. Increasing S can increase ZT, by increasing , or by decreasing .…”
Section: Introductionmentioning
confidence: 99%